If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x = 4x + -6 Reorder the terms: 6x = -6 + 4x Solving 6x = -6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6x + -4x = -6 + 4x + -4x Combine like terms: 6x + -4x = 2x 2x = -6 + 4x + -4x Combine like terms: 4x + -4x = 0 2x = -6 + 0 2x = -6 Divide each side by '2'. x = -3 Simplifying x = -3
| 15000-500x+4x^2=10400 | | 6g+4=58 | | -5x^2-38x-21=0 | | 2(q-4)=6 | | 3x=3*2+x*2 | | 4y+3=-3+2y+14 | | 2.25=qt | | 1-3x=2(-4x+7) | | 4a+2b=5 | | -10=-4+2k | | -5(x-4)-9=11 | | 14=8+2p | | 7(2x+5)=4x | | 10b^2-11b+3=0 | | 16=3s-4 | | 5+7i^2= | | (5x^2-7x-2)+(9x^2+8x-4)= | | 5(3y-1)-3(2x)=19 | | 6+3s=-9 | | 3m^2+6=-36 | | 3q+1=10 | | 2(n-6)=24 | | -6x+4=-4(2x+3) | | 2+3(x+1)=5x+5 | | 3(4x-3.2)=8x-9.6 | | 6+4f=46 | | 7.5(k-5)=22.5 | | y=2x^2+10 | | Y=-0.2X+33 | | a^2-10a+25=49 | | Y=-0.2X+30 | | Y=0.2X+33 |